(untitled) (Academicia Globe: Inderscience Research, 2024)
In this article, the issues of interdependence of the cities and villages of South Uzbekistan, i.e., the origin of the term "village", "village", the fact that the artisan layer of semi-nomadic tribes operated in a more sedentary state than nomadism, the fact that the rural population is fully engaged in agriculture, and cities are the first in large cities Based on historical sources, the factors of the formation of rabots reflecting the main characteristics of medieval urbanism, the fact that behind the defensive walls of the cities, nearby and neighboring villages started the process of formation of rabots before the arrival of the Arabs, and the factors of their popularity as a craft center were analyzed.